UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MATERI POKOK BILANGAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS VII.1 SMPN 3 BATUSANGKAR - Defison Defison (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTBased on the learning outcomes of Class VII students. 1SMPN 3 Batusangkar in Mathematics Subjects Principal Numbers found that student learning outcomes in Mathematics Principal Material Subjects Numbers are still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in Mathematics Subject matter in Numbers through the STAD Type Cooperative Learning Model in Class VII. 1SMPN 3 Batusangkar Tanah Datar District. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 23 students of Class VII.1 SMPN 3 Batusangkar. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the Cooperative Learning Model STAD Type can improve student learning outcomes in the Principal Numbers Mathematics subject at Batusangkar 3 Public Middle School. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle were 66.78 (sufficient), increasing to 82.59 (good) with an increase of 15.81%.